Considerations for Dose Selection and Clinical Pharmacokinetics/Pharmacodynamics for the Development of Antibacterial Agents - Rizk, M. L. (Antimicrob Agents Chemother, 2019)
In June 2017, The National Institute of Allergy and Infectious Diseases, part of the National Institutes of Health, organized a workshop entitled “Pharmacokinetics-Pharmacodynamics (PK/PD) for Development of Therapeutics against Bacterial Pathogens” to discuss details and critical parameters of various PK/PD methods and identify approaches for linking human pharmacokinetic (PK) data and drug efficacy analyses. The workshop participants included individuals from academia, industry, and government. This and the accompanying minireview on nonclinical PK/PD summarize the workshop discussions and recommendations. It is important to consider how information like PK/PD can support the clinical effectiveness of new antibacterial drugs, as PK/PD data have become central to antibacterial drug development programs. Key clinical considerations for antibacterial dose selection and clinical PK/PD characterization discussed in this minireview include a robust assessment of PK in the patient population of interest, critical considerations for assessing drug penetration in the lung for the treatment of pneumonia, and an emphasis on special populations, including patients with renal impairment and augmented renal function, as well as on dosing in obese and pediatric patients. Successful application of such approaches is now used to provide a more informative drug development package to support the approval of new antibiotics.